Development of a limited sampling strategy for the estimation of isoniazid exposure considering N-acetyltransferase 2 genotypes in Korean patients with tuberculosis. (March 2021) - Lee, Jihyun; Choi, Giwon; Yang, Seungwon; Ha, Jung-Eun; Kim, Eun Sun; Park, Jong Sun; Lee, Kyunghoon; Song, Junghan; Lee, Jae Ho; Lee, Jangik I.
Abstract: A limited sampling strategy (LSS) to estimate the exposure to isoniazid was developed considering N-acetyltransferase 2 ( NAT2 ) genotypes in Korean patients with tuberculosis. The influence of the genotypes on the pharmacokinetics of isoniazid was also evaluated. A total of 33 participants participated in the study and received isoniazid 300 mg once daily. Evaluable participants consist of ten slow (SA), fourteen intermediate (IA) and six rapid acetylators (RA). As expected, isoniazid exposure was higher (mean AUC, 28.4 versus 7.6 mg*h/L) and systemic clearance lower (mean apparent clearance, 14.8 versus 50.6 L/h) in SAs than RAs. The formulas to estimate isoniazid exposure were constructed using one or more concentration-time points that correlate with the area under the concentration-time curve (AUC). The LSS using a formula of single concentration-time point at 4 h post dose (C4 ) is applicable for all acetylators to the therapeutic drug monitoring (TDM) of isoniazid in patients with tuberculosis when evaluated using the Deming regression and Bland-Altman plot (AUC = 1.53 + 10.03*C4, adjusted r 2 = 0.95, p < 0.001). Considering that SAs are more prone to adverse effects, pre-dose NAT2 genotyping would be valuable for optimal isoniazid dosing in conjunction with TDM.